1997
DOI: 10.1128/jb.179.24.7759-7767.1997
|View full text |Cite
|
Sign up to set email alerts
|

Myxococcus xanthus sasS encodes a sensor histidine kinase required for early developmental gene expression

Abstract: Initiation of Myxococcus xanthus multicellular development requires integration of information concerning the cells' nutrient status and density. A gain-of-function mutation, sasB7, that bypasses both the starvation and high cell density requirements for developmental expression of the 4521 reporter gene, maps to the sasS gene. The wild-type sasS gene was cloned and sequenced. This gene is predicted to encode a sensor histidine protein kinase that appears to be a key element in the transduction of starvation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…The results suggested that A-signaling is required in the first few hours of development for the expression of most developmental genes. The response to A-signaling involves the SasS-SasRSasN histidine kinase-response regulator-negative regulator three-component signal transduction system (59,60). By measuring expression of Tn5 lac fusions in a csgA mutant, it was revealed that C-signaling begins to be required at about 6 h into development (27).…”
mentioning
confidence: 99%
“…The results suggested that A-signaling is required in the first few hours of development for the expression of most developmental genes. The response to A-signaling involves the SasS-SasRSasN histidine kinase-response regulator-negative regulator three-component signal transduction system (59,60). By measuring expression of Tn5 lac fusions in a csgA mutant, it was revealed that C-signaling begins to be required at about 6 h into development (27).…”
mentioning
confidence: 99%
“…Through extensive genetic and biochemical studies, a number of regulatory proteins thought to be involved in cellular aggregation and sporulation, including two-component proteins, such as histidine kinases and response regulators, serine threonine kinases, sigma factors and their associated transcriptional factors, and other proteins with no homology to known proteins, have been identified (2,7,8,9,10,13,14,33,42,47). In this study we have focused on a putative 54 activator that may play an important role in M. xanthus developmental gene regulation.…”
mentioning
confidence: 99%
“…H. Kaplan (University of Texas-Houston) has used lacZ fusions to genes induced early during development in screens for mutants. This approach initially uncovered a two-component system (SasS/ SasR) that senses and responds to A signal, a cell density signal composed of peptides and amino acids generated by extracellular M. xanthus proteases at the onset of development (35,129). A third component, SasN, inhibits SasS/SasR during growth, providing a nutritional status input that does not depend on cell density (128).…”
Section: Vol 185 2003mentioning
confidence: 99%